Adsorption behaviours of sulfonated humic acid at fly ash‐water interface: Investigation of equilibrium and kinetic characteristics. (4th September 2015) - Yang, Siqi; Huang, Guohe; An, Chunjiang; Li, Huiqin; Shi, Yarong
Abstract Sulfonated humic acid (SHA) has been widely used in oilfield production and it can significantly contribute to COD, BOD, sulphurated pollutants, and other toxic substances when discharged into the environment. There is an urgent need for effective and safe remediation of such toxic compounds from wastewater. This study investigated the adsorption characteristics of SHA onto coal fly ash. The removal percentage increased with fly ash dosages up to 1 and 6 g/L for Shand and BD fly ash, respectively, and it reached a constant level at a certain fly ash dosage. The Langmuir isotherm model could better fit equilibrium data for the adsorption of SHA on fly ash. Kinetic analysis showed that this process can be described well by a pseudo‐second‐order model. The adsorption of SHA on fly ash was improved by increasing temperature from 15 to 35 °C, and the thermodynamics results indicated that the adsorption was endothermic in nature. In addition, both ionic strength and pH had an influence on the adsorption performance. Fly ash showed the potential to be an effective adsorbent for the removal of SHA from an aqueous phase. The results can be used to reveal the migration patterns of organic contaminants at the fly ash surface.